Pengaruh Kualitas Pelayanan dan Pengalaman Pelanggan Terhadap Loyalitas Pelanggan Shopee di Kota Singaraja - I Gusti Agung Ayu Suryantini; I Nyoman Sujana (Ekuitas: Jurnal Pendidikan Ekonomi, 2023)
This study aims to determine: (1) the effect of service quality on shopee customer loyalty in Singaraja City, (2) the effect of customer experience on shopee customer loyalty in Singaraja City, and (3) the effect of service quality and customer experience on shopee customer loyalty in Singaraja City. The type of research used is causality. The population in this study are the users of the shopee application in Singaraja City. Determination of the sample in this study was carried out by purposive sampling method with certain criteria so as to obtain a total sample of 105 respondents. The type of data used is quantitative data. Sources of data used in this study are primary and secondary data. The data collection method used in this study was a questionnaire method. The data analysis technique used in this study is multiple linear regression analysis and uses the classical assumption test, t test, F test and coefficient of determination test. The results of this study indicate that: (1) service quality has a partial and positive effect on customer loyalty, (2) customer experience has a partial and positive effect on customer loyalty, and (3) service quality and customer experience have a simultaneous effect on customer loyalty.